Sequence stratigraphy of a tidally dominated carbonate-siliciclastic ramp; the Tithonian-Early Berriasian of the southern Neuquen Basin, Argentina - Spalletti, Luis Antonio (2000)
The Tithonian-Berriasian Vaca Muerta, Carrin Cura and Picun Leufu formations in the southern Neuquen Basin were deposited on a tidally dominated, mixed carbonate-siliciclastic ramp. Basinal, outer, middle, shallow and back ramp facies associations are recognized and a sequence stratigraphic analysis reveals that the ramp record consists of three shallowing-upwards sequences (Ti1, Ti2 and Ti3) set within a lower-order progradational cycle. A higher order of cyclicity is superimposed on to the middle (Ti2) sequence. The majority of the ramp facies belong to the transgressive and highstand systems tracts; however, at the base of Ti2, a lowstand systems tract is identified, characterized by a basal unconformity and an abrupt basinward shift of the shallow marine lithofacies. Transgressive systems tracts were characterized by slow sedimentation rates and rapid sea-level rises that affected carbonate productivity. Highstand systems tracts show the greatest carbonate productivity and an increased progradation rate on account of a reduction in accommodation space generation. Palaeogeography played a major role in the development of the depositional systems. Partial isolation from the Pacific Ocean reflecting the growth of the Andean magmatic arc and geographic restriction due to tectonic inversion in the central part of the basin resulted in a meso-macrotidal regime that produced a tidally dominated sedimentary record in the shallow and back ramp environments. Coeval anoxic conditions in the central part of the Neuquen Basin favoured distal ramp and basinal black shale deposition during episodes of relative sea-level rise.